Konstruksi Sosial Drama Layang Putus: Studi Social Learning Ibu Rumah Tangga Di Kota Palopo - Syarifuddin Syarifuddin; Aswan Aswan (Contemporary Education Review, 2025)
This study discusses the social construction of the drama Layangan Putus as social learning for housewives in Bara District, Palopo City. The purpose of this study is to understand how the Layangan Putus drama constructs the reality of housewives in Bara District, Palopo City. To understand the social learning from the Layangan Putus drama for housewives in Bara District, Palopo City. This study is a descriptive qualitative research using a communication approach with social construction theory and social learning theory. The informants used were eight housewives. Data was collected through observation, interviews, and documentation. The results of this study indicate that the drama Layangan Putus generates discourse about spousal relationships and domestic conflicts. The drama Layangan Putus has constructed housewives up to the stage of internalization dialectics, Society has now developed a broader understanding of how to address external realities and does not immediately create new realities. By observing the scenes in the Layangan Putus drama and evaluating each event and the course of Aris's affair, culminating in Kinan's proof of her husband's infidelity, and ultimately ending in the divorce between Aris and Kinan. The social lesson learned by housewives after watching the drama Layangan Putus is that romantic gestures, previously considered a sign of a partner's loyalty, are in fact the opposite. The drama shows that a husband's romantic gestures are actually a factor that triggers him to cheat on his wife, covering up his infidelity with romantic gestures towards his wife